A universal incision for robot-assisted thoracic surgery - Jiao, Jia; Guo, Jinbao; Zhao, Jia; Li, Xiangnan; Du, Ming (Frontiers in Surgery, 2022)
Objective This paper aimed to design and explore the versatility of the incision for the robot-assisted thoracic surgery. Methods The concept of universal incision was designed and put forward. The clinical data of 342 cases of robot-assisted thoracic surgery were summarized, including sex, age, clinical diagnosis, operative method, operative time, conversion to thoracotomy, intraoperative blood loss, number of lymph node dissections, postoperative hospital stays, postoperative pathology, and postoperative complications of the patients. Results The 342 cases of robot-assisted surgery included 178 pulmonary surgery cases (94 lobectomy cases, 75 segmentectomy cases, 6 wedge resection cases, and 3 sleeve lobectomy cases), 112 esophageal surgery cases (107 McKeown approach cases and 5 esophageal leiomyoma resection cases), and 52 mediastinal tumor cases (42 anterior mediastinum cases and 10 posterior mediastinum cases). Among these, two cases were converted to thoracotomy (both esophageal cases), and the rest were successful with no massive intraoperative bleeding and no perioperative death. Conclusion The universal incision of robot-assisted thoracic surgery is safe and feasible and is suitable for most cases of thoracic surgery.